Effectiveness of Nanopriming Using Padina minor Nanoparticles on the Germination and Early Growth of Kopay Chili Pepper Seeds (Capsicum annuum L.) - Winny Rabbial Firsti Aswendri; Suwirmen; Zozy Aneloi Noli (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to evaluate the effects of nanopriming using Padina minor nanoparticles on the germination parameters and early seedling growth of Kopay chili pepper (Capsicum annuum L.) seeds, as well as to assess the physiological responses and enzyme activities associated with nanopriming treatment. The experiment was arranged in a completely randomized design (CRD) with five treatments: no priming, hydropriming, and nanopriming at concentrations of 100, 150, and 200 ppm, each with five replications. The observed parameters included time to germination emergence, germination potential, vigor index, root length, shoot length, and the activities of amylase and catalase enzymes. Data were analyzed using analysis of variance (ANOVA) at the 5% significance level, followed by Duncan’s Multiple Range Test (DMRT). The results showed that nanopriming significantly accelerated germination emergence and increased root length, with the best response observed at 100 ppm. However, the treatment did not have a significant effect on germination potential, vigor index, shoot length, or the activities of amylase and catalase during the early germination phase. Thus, Padina minor nanopriming contributes to the improvement of specific early growth parameters, particularly those related to germination speed and root development.